2022
DOI: 10.25259/jrhm_8_2022
|View full text |Cite
|
Sign up to set email alerts
|

RISUG® offers early contraception: An experience during Phase III clinical trials

Abstract: Objectives: An early contraceptive efficacy with reasonable assurance of reversibility has been a challenge in male contraception. With nearly four decades of research in reversible inhibition of sperm under guidance (RISUG®) as an intravasal male contraceptive, including pre-clinical trials in rats, rabbits, langur monkeys, and three phases of clinical trials, the present study aims to evaluate the additional parameters of a center of Phase III clinical trials. Material and Methods: Subjects were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Phase 1 and 2 trials of RISUG were published in 1993 and 1997, respectively [ 94 95 ]. In 2002, the test was stopped due to toxicity, but it was resumed in 2003 as an extended phase 3 trial [ 96 ]. The results have shown considerable potential, with administration through a single injection, complete reversibility, and 96.7% efficacy after 6 months [ 92 97 ].…”
Section: Male Contraception In Research and Developmentmentioning
confidence: 99%
“…Phase 1 and 2 trials of RISUG were published in 1993 and 1997, respectively [ 94 95 ]. In 2002, the test was stopped due to toxicity, but it was resumed in 2003 as an extended phase 3 trial [ 96 ]. The results have shown considerable potential, with administration through a single injection, complete reversibility, and 96.7% efficacy after 6 months [ 92 97 ].…”
Section: Male Contraception In Research and Developmentmentioning
confidence: 99%
“…53 Similarly, a study done in 2022 demonstrated efficacy of RISUG of vas occlusion and its reversibility in a group of 28 males. 54 A DOUBLE STANDARD? To date, numerous studies have demonstrated nearly complete reversible suppression of spermatogenesis using intramuscular injection-based testosterone esters.…”
Section: Future Directionsmentioning
confidence: 99%